Utilizing population-based clinical and administrative data to explore the relevance of frailty to cholinesterase inhibitor use and discontinuation at nursing home transition. (2018) - Maclagan, Laura; Maxwell, Colleen; Guan, Jun; Campitelli, Michael; Herrmann, Nathan; Lapane, Kate; Hogan, David; Amuah, Joseph; Seitz, Dallas; Gill, Sudeep; Bronskill, Susan
No abstract available